Systemic Immune-Inflammation Index and Systemic Inflammation Response Index Predict the Response to Radioiodine Therapy for Differentiated Thyroid Cancer - Wang Y; Chang J; Hu B; Yang S (Dove Medical Press, 2024)
Yan Wang,1,2 Junshun Chang,1 Ben Hu,3 Suyun Yang1 1Department of Nuclear Medicine, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030001, People's Republic of China; 2Academy of Medical Sciences, Shanxi Medical University, Taiyuan, Shanxi, 030001, People's Republic of China; 3The Fifth Clinical Medical School of Anhui Medical University, Hefei, Anhui, People's Republic of ChinaCorrespondence: Ben Hu; Suyun Yang, Email a917744537@163.com; wangyan86@sxmu.edu.cnPurpose: This research sought to evaluate the clinical value of systemic immune-inflammation index and systemic inflammation response index in predicting the response to radioactive iodine (RAI) therapy in individuals diagnosed with differentiated thyroid cancer.Patients and Methods: This retrospective study included 406 patients with differentiated thyroid cancer who received initial RAI therapy and follow-up from December 2019 to December 2023. Patients were divided into two groups based on imaging and serum indicators to evaluate the response to radioactive iodine treatment: the ER group (excellent response) and the non-ER group (suboptimal response). Systemic immune-inflammation index and systemic inflammation response index were calculated based on peripheral blood cell counts before treatment. Multivariable logistic regression analysis was used to assess the independent associations of these indices with the therapeutic response to radioiodine treatment. Receiver operating characteristic (ROC) curves were graphed and the area under the curve (AUC) was calculated to evaluate their predictive ability.Results: Compared to the ER group, patients in the non-ER group had significantly elevated systemic immune-inflammation index and systemic inflammation response index levels (p < 0.001). After adjusting for confounding factors, there was a significant association between these indices and the response to radioactive iodine treatment in patients with differentiated thyroid cancer. The optimal cutoff values for predicting the response to RAI treatment were 668.91 for systemic immune-inflammation index (AUC=0.692, sensitivity 58.2%, specificity 73.1%, 95% CI: 0.639- 0.745, p < 0.001) and 0.47 for systemic inflammation response index (AUC=0.664, sensitivity 85.6%, specificity 42.7%, 95% CI: 0.612- 0.717, p < 0.001).Conclusion: Systemic immune-inflammation index and systemic inflammation response index could be valuable for predicting the response to RAI treatment in individuals diagnosed with differentiated thyroid cancer. Further research is needed to explore their practical utility, and these novel inflammation markers could serve as adjunct tools in clinical practice.Keywords: systemic immune-inflammation index, systemic inflammation response index, differentiated thyroid cancer, radioactive iodine therapy